Molecular features of heterogeneous vancomycin-intermediate Staphylococcus aureus strains isolated from bacteremic patients - Belausov Natasha; Nitzan Yeshayahu; Zlotkin Amir; Lago Levona; Maor Yasmin; Ben-David Debby; Keller Nathan; Rahav Galia (BMC Microbiology, 2009)
Abstract Background Heterogeneous vancomycin-intermediate Staphylococcus aureus (hVISA) bacteremia is an emerging infection. Our objective was to determine the molecular features of hVISA strains isolated from bacteremic patients and to compare them to methicillin resistant S. aureus (MRSA) and methicillin sensitive S. aureus (MSSA) blood isolates. Results We assessed phenotypic and genomic changes of hVISA (n = 24), MRSA (n = 16) and MSSA (n = 17) isolates by PCR to determine staphylococcal chromosomal cassette (SCCmec) types, Panton-Valentine leukocidin (PVL) and the accessory gene regulator (agr) loci. Biofilm formation was quantified. Genetic relatedness was assessed by PFGE. PFGE analysis of isolates was diverse suggesting multiple sources of infection. 50% of hVISA isolates carried SCCmec type I, 21% type II; 25% type V; in 4% the SCCmec type could not be identified. Among MRSA isolates, 44% were SCCmec type I, 12.5% type II, 25% type V, 12.5% were non-typable, and 6% were SCCmec type IVd. Only one hVISA isolate and two MSSA isolates carried the PVL. Biofilm formation and agr patterns were diverse. Conclusion hVISA isolates were diverse in all parameters tested. A considerable number of hVISA and MRSA strains carried the SCCmec type V cassette, which was not related to community acquisition.